1992
DOI: 10.1007/bf01799620
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked adrenoleukodystrophy: Biochemical diagnosis and enzyme defect

Abstract: The adrenoleukodystrophies refer to three genetically distinct disorders all characterized by the accumulation of very long-chain fatty acids. In this paper we will review the biochemical aspects of these leukodystrophies with particular emphasis on the methods used to measure very long-chain fatty acid levels in plasma and their reliability. Furthermore, we will concentrate on the primary defect in the X-linked form of adrenoleukodystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 48 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…His plasma VLCFA levels were within normal limits, whereas those in cultured skin fibroblasts were characteristic of X-ALD. We were sur- 11,814 women who were free of disorders that involve the peroxisome. Note that there is a greater degree of overlap between X-ALD and the controls than in the male population (see Fig 2) and that application of a discriminant function does not eliminate the overlap.…”
Section: Do False-negative Results Occur?mentioning
confidence: 99%
“…His plasma VLCFA levels were within normal limits, whereas those in cultured skin fibroblasts were characteristic of X-ALD. We were sur- 11,814 women who were free of disorders that involve the peroxisome. Note that there is a greater degree of overlap between X-ALD and the controls than in the male population (see Fig 2) and that application of a discriminant function does not eliminate the overlap.…”
Section: Do False-negative Results Occur?mentioning
confidence: 99%
“…Other studies demonstrated that treatment with Lorenzo's Oil was ineffective in changing the clinical course of the disease in 15 Italian and 20 American boys with ALD, who already presented neurologic symptoms at diagnosis (Wanders et al, 1992;Moser et al, 1992). In addition, Korenke et al (1995) assessed the results of treatment with the GTO/GTE mixture in 16 patients, 7 of them asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…The major accumulated saturated fatty acids are hexacosanoic acid (C 26:0 ) and tetracosanoic acid (C 24:0 ) Korenke et al, 1995). The increased concentrations of these metabolites cause progressive demyelination of white matter in the central nervous system and adrenal insufficiency (Wanders et al, 1992;Ruiz, 1996;Moser, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, as previously mentioned, more favorable prognosis depends on treatment beginning before neurological symptoms appear (Moser et al, 1994;Moser, 1995;Korenke et al, 1995). In 15 Italian ALD boys and 20 American ALD boys presenting neurological symptoms, Lorenzo's oil therapy failed to change the clinical course of the disease (Wanders et al, 1992;Moser et al, 1992). Korenke et al (1995) studied 16 patients treated with Lorenzo's oil during 19 months.…”
Section: Resultsmentioning
confidence: 99%
“…It should be differentiated clinically and biochemically from neonatal ALD, an autosomal recessive disorder of peroxisome biogenesis in which the function of at least five peroxisomal enzymes is impaired. In X-ALD, a defect in lignoceroyl-CoA ligase causes pathognomonic tissue accumulation of very long chain fatty acids (VLCFA), mainly hexacosanoic (C26:0) and tetracosanoic acids (C24:0) (Wanders et al, 1988(Wanders et al, , 1992Moser, 1993). Fatty acid accumulation seems responsible for adrenal cortex malfunction and nervous system demyelination Wanders et al, 1996).…”
Section: Introductionmentioning
confidence: 99%